Seizures in a young adult Nigerian maleabusing codeine containing cough syrup - Raji, Saheed; Inogbo, Chinwe; Oriji, Sunday; James, Bawo (Nigerian Journal of Basic and Clinical Sciences, 2026)
Cough remedies are available in Nigeria as narcotic and nonnarcotic over-the-counter preparations. The narcotic antitussive usually contains codeine, which has a high abuse potential. We report a case of a young Nigerian male, abusing codeine containing cough syrup with a clinical picture complicated by seizures, as well as review of relevant and available literature, including a discussion of its implication for clinical care. Clinicians should be aware of abuse and dependent potential of codeine containing cough syrup with seizures as one of the possible feature of toxicity. This case report buttresses the need for codeine containing cough syrups to be made available only on prescription.